The value perspective to adopt mobile banking - Bojei, Jamil; Alsheikh, Laila (Universiti Putra Malaysia Press, 2013)
Customer’s value perception is a subjective concept in banking services. Value perception varies among bank customers. Despite the availability of technologically advanced mobile devices, mobile banking services, which use these devices, have not been widely accepted by the customers. Thus, the objective of this study is to investigate various factors affecting the value held by bank customers in driving their behavioural intention to use mobile banking services. The findings from this study may enable banks which seek to promote competitive advantage to examine all factors related to perceived value in order to improve customer value of mobile banking service and consequently their intention to adopt.